Associations between pre-stroke physical activity and physical quality of life three months after stroke in patients with mild disability. - Melanie Zirnsak; Christine Meisinger; Jakob Linseisen; Michael Ertl; Philipp Zickler; Markus Naumann; Inge Kirchberger (PLoS ONE, 2022)
Background Much is known about the association between physical activity and the occurrence of stroke. However, the evidence about the correlation between pre-stroke physical activity and post-stroke quality of life remains inconsistent. Thus, there is a high public health relevance to the topic. Aim The aim of this study was to investigate the association between pre-stroke physical activity and physical quality of life after three months. Methods Data arises from 858 patients with stroke included a prospective single-centre observational cohort study in Augsburg, Germany, between September 2018 and November 2019. The participants were recruited at the Department of Neurology and Clinical Neurophysiology, University Hospital of Augsburg after their stroke event. The level of physical activity was determined following the short form of the International Physical Activity Questionnaire at baseline. Physical quality of life was assessed three months after hospital discharge using the German version of the Stroke Impact Scale (SIS). A multiple linear regression model and a quantile regression were carried out. Results A total of 497 patients were included in the analysis (mean age 69.6, 58.8% male), 26.2% had a high, 18.9% a moderate and 54.9% a low level of pre-stroke physical activity. Patients with high pre-stroke physical activity had a significantly better physical quality of life three months after stroke in the SIS physical domain (beta = 4.1) and in the SIS subdomains hand function (beta = 5.6), mobility (beta = 4.1) and activities of daily living (beta = 3.7). In the physical domain and the subdomain mobility, the effect was especially strong for persons with low physical quality of life after three months. Conclusion Pre-stroke physical activity seems to have an important and positive association with physical quality of life after three months in patients with mild disability. Further studies are needed to confirm these results.